Efficient Ligation of the Schistosoma Hammerhead Ribozyme - Canny, Marella D. (2007)
The hammerhead ribozyme from Schistosoma mansoni is the best characterized of the natural hammerhead ribozymes. Biophysical, biochemical, and structural studies have shown that the formation of the loop-loop tertiary interaction between stems I and II alters the global folding, cleavage kinetics, and conformation of the catalytic core of this hammerhead, leading to a ribozyme that is readily cleaved under physiological conditions. This study investigates the ligation kinetics and the internal equilibrium between cleavage and ligation for the Schistosoma hammerhead. Single turnover kinetic studies on a construct where the ribozyme cleaves and ligates substrate(s) in trans showed up to 23% ligation when starting from fully cleaved products. This was achieved by a ~2,000-fold increase in the rate of ligation compared to a minimal hammerhead without the loop-loop tertiary interaction, yielding an internal equilibrium that ranges from 2–3 at physiological Mg(2+) ion concentrations (0.1 –1 mM). Thus, the natural Schistosoma hammerhead ribozyme is almost as efficient at ligation as it is at cleavage. The results here are consistent with a model where formation of the loop-loop tertiary interaction leads to a higher population of catalytically active molecules, and where formation of this tertiary interaction has a much larger effect on the ligation than the cleavage activity of the Schistosoma hammerhead ribozyme.